2018
DOI: 10.1093/ptep/pty055
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of QCD chaos in linear sigma models and holography

Abstract: Measuring chaos of QCD-like theories is a challenge for formulating a novel characterization of quantum gauge theories. We define a chaos phase diagram of QCD allowing us to locate chaos in the parameter space of energy of homogeneous meson condensates and the QCD parameters such as pion/quark mass. We draw the chaos phase diagrams obtained in two ways: first, by using a linear sigma model, varying parameters of the potential, and second, by using the D4/D6 holographic QCD, varying the number of colors N c and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This was a motivation for the model of[18], and string theory matrix models in similar spirit are found in[47][48][49][50] 4. For related chaos analyses, see[52][53][54] 5.…”
mentioning
confidence: 76%
“…This was a motivation for the model of[18], and string theory matrix models in similar spirit are found in[47][48][49][50] 4. For related chaos analyses, see[52][53][54] 5.…”
mentioning
confidence: 76%
“…For example, in the Sachdev-Ye-Kitaev (SYK) model, it was confirmed that the bound is saturated. The Lyapunov exponent in gravity systems has been extensively studied (and also [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]). For a test particle, the Lyapunov exponents in static and spherically symmetric spacetimes [17,19,23,27,28,38,39,41], rotating black hole spacetimes [13,19,24,30], the magnetized Ernst-Schwarzschild spacetime [18], multi-black hole spacetimes [20], the Myers-Perry black hole spacetime [26,41], the Einstein-Maxwell-dilaton gravity [32,39], and a black hole with quasi-topological electromagnetism [40] have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a possible explanation of quantum chaos in the hadronic spectrum by a holographic approach can be found in [14]. Probing the phase diagram of QCD chaos is a challenging task, an option effectively explored in [15].…”
Section: Introductionmentioning
confidence: 99%